INSTAGRAM SOCIAL MEDIA TRAINING TO INTRODUCE THE BRAWIJAYA MUSEUM COLLECTIONS TO THE DIGITAL PUBLIC - Sri Pandanari, Dika; Kabir, Gedong; Windaningsih; Setyowibowo, Bhekti; Dhamayanti, Meilani (SEEIJ (Social Economics and Ecology International Journal), 2026)
Brawijaya Museum is a military history center in Malang City that has a wealth of valuable collections. Unfortunately, this museum is not yet fully known by the digital community. Limitations in digital communication strategies, especially through social media, have limited the museum's reach to visits by educational institutions such as student groups facilitated by teachers. This community service activity aims to provide training in the use of social media, especially Instagram, to the management of the Brawijaya Museum to increase the visibility and appeal of the museum's collections to the wider public. The methods used in this activity include technical training, assistance in creating visual content and interactive narratives, optimizing Instagram features, and preparing guidelines for implementing Instagram social media management for the sustainability of the museum's existence on social media. The active participation of partners in each stage of the activity strengthens the sustainability of the program, while increasing their capacity to manage digital media independently. The results of this activity show an increase in the ability of partners to produce and manage content on Instagram, as well as the preparation of a digital communication strategy for managers. This activity is expected to be a model for strengthening digital capacity for other institutions in reaching the digital community more effectively